Identifikasi Label Kode Leadframe pada Sistem Uji Fungsi RFID Chip Berbasis Template Matching - Nanta Fakih Prebianto; Ikhwan Heprilnez Pratama; Nur Sakinah Asaad; Anugerah Wibisana; Hendawan Soebhakti (Journal of Applied Electrical Engineering, 2023)
The label code in a production process has an important function as an identifier. Making label code on leadframe can be done by laser engraving or painting method. The RFID chip is moved to the leadframe media to carry the signal from the die level to the outside circuit. The conductivity function test is carried out to ensure the circuit works after the die attach and wire bond processes from the RFID chip. Based on the case study on TFME, the results of this function test are stored with manual labeling. The template matching method is applied to read the leadframe label code which will then be scanned in the form of a test technical report. This label identification system uses a Raspberry Pi 3 equipped with a Sony IMX219V2 camera with a resolution of 8 MP. 2 characters that are similar, namely numbers 2 and Z, are eliminated from the sample. In addition, the label code is made in characters with vertical and horizontal lines. In this result, a success rate of 100%. This identified label code then becomes the leadframe identification number in the form of a report file that is stored in a document format.